Preparation method of high-strength open-cell material and product and application of high-strength open-cell material

By introducing low-reactive magnesium oxide and phosphate into the polymer composite material and forming bone cement through water immersion, the problem of polymer material strength reduction caused by the cell structure is solved, and high strength and toughness are achieved.

CN119591931AActive Publication Date: 2025-03-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311160834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

After the introduction of the cell structure, the strength of the polymer material will be significantly reduced, making it difficult to take into account both toughness and strength.

Method used

Unreacted low-reactive magnesium oxide and phosphate are introduced into the unfoamed polymer composite material, and the magnesium oxide and phosphate are reacted through water immersion to form bone cement, thereby improving the strength of the porous material.

Benefits of technology

Through this method, the strength of the open-cell material is significantly improved, the strength reduction problem caused by the cell structure is solved, and the toughness of the material is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591931A_ABST
    Figure CN119591931A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength open-cell material, and a product and application thereof. 85-99.99 parts by mass of polymer resin and 0.01-15 parts by mass of powder are mixed, melted and extruded to obtain a composite material; the polymer resin and the powder phase are dewatered before being used until the water content is less than 0.01 wt%; the powder phase comprises low-activity magnesium oxide and phosphate in a mass ratio of 1: (3-5); the phosphate is at least one of dihydric phosphate and monohydric phosphate; the low-activity magnesium oxide is obtained by heating magnesium oxide to 1400-1600 DEG C at a heating rate of not more than 10 DEG C / min and keeping the temperature for 3-6 hours; performing saturation treatment on the composite material in a physical foaming agent to obtain a saturated system, and performing pressure relief foaming to obtain an open-cell material; the pressure of the physical foaming agent is 5-25 MPa; the pressure relief foaming pressure relief rate is 10-100 MPa / s; immersing the open-cell material into water, and reacting the low-activity magnesium oxide with phosphate to generate bone cement, so that the strength of the open-cell material is improved, and the high-strength open-cell material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer open-cell materials, and in particular to a preparation method of a high-strength open-cell material and a product and application thereof. Background Art

[0002] Physical foaming is a common method for preparing polymer open-cell materials.

[0003] For example, the patent specification with publication number CN114752097A discloses a method for preparing a polylactic acid foam material with an open-cell structure by using a supercritical carbon dioxide intermittent foaming method, the steps of which are as follows: (1) melt and plasticize polylactic acid pellets above their melting point, and hot press them into a sheet material of suitable thickness; (2) cut the polylactic acid sheet to an appropriate size and place it in a fixture to limit the direction of its foam growth; (3) place the polylactic acid sheet fixed by the fixture into a foaming kettle, and use a high-pressure injection pump to pass a supercritical fluid; (4) heat the foaming kettle, wait until the temperature reaches the specified foaming temperature, the gas pressure reaches the set value, fully saturate for a period of time, allow the gas to diffuse into the polylactic acid matrix, and reach an equilibrium state; (5) open the foaming kettle pressure relief valve instantly after the saturation is completed, break the equilibrium state of the system, make the polylactic acid foam, and obtain a bio-based polylactic acid open-cell foam material. The open-cell polylactic acid foam prepared by this patented technology has an open cell rate of more than 85% and an expansion ratio of 15-30 times.

[0004] For another example, the patent specification with publication number CN113736128A discloses a polylactic acid-based foaming material and a preparation method thereof, the preparation method comprising: subjecting a polylactic acid substrate to a saturation treatment in a foaming gas to obtain a saturated system, wherein the polylactic acid substrate comprises stereocomposite crystals and homogeneous crystals, and the crystallinity of the stereocomposite crystals is greater than or equal to 15%, the saturation treatment comprising a first saturation stage and a second saturation stage, the temperature of the first saturation stage is greater than or equal to the melting temperature of the homogeneous crystals and less than the melting temperature of the stereocomposite crystals, and the temperature of the second saturation stage is less than the temperature of the first saturation stage; then, the saturated system is subjected to pressure relief and foaming to obtain a polylactic acid-based foaming material, wherein the sum of the crystallinity of the stereocomposite crystals and the crystallinity of the homogeneous crystals in the polylactic acid-based foaming material is greater than or equal to 40%. This patented technology divides the saturation treatment of the polylactic acid substrate into two stages, and controls the temperature of the first saturation stage and the second saturation stage respectively, so that the obtained saturated system absorbs more saturated gas and has a suitable melt strength. Therefore, when the pressure is released and foamed, the bubbles can grow well, and then a polylactic acid-based foaming material with a high expansion ratio is obtained. When this patented technology is implemented specifically: the absolute value of the difference between the temperature of the first saturation stage and the melting temperature of the homogeneous crystal is 5 to 30°C; the pressure of the foaming gas is 10.0 to 25.0MPa; the cooling rate from the first saturation stage to the second saturation stage is 1 to 30°C / min; in the step of relieving the pressure of the saturated system for foaming, the pressure relief rate is 20.0 to 100.0MPa / s.

[0005] However, in actual situations, although the introduction of the pore structure will increase the toughness of the polymer material, its strength will be significantly reduced. Summary of the invention

[0006] In view of the above-mentioned technical problems and the shortcomings in the art, the present invention provides a method for preparing a high-strength open-pored material, by introducing unreacted low-activity magnesium oxide and phosphate into an unfoamed polymer composite material, preparing the composite material into an open-pored material, and then immersing the composite material in water. The interconnected pore structure is utilized to allow the magnesium oxide and phosphate to fully contact the water, thereby promoting the reaction of the magnesium oxide and phosphate into bone cement, thereby improving the strength of the open-pored material.

[0007] The specific technical solutions are as follows:

[0008] A method for preparing a high-strength open-pored material comprises the following steps:

[0009] S1, mixing 85-99.99 parts by weight of a polymer resin and 0.01-15 parts by weight of a powder phase and melt-extruding to obtain a composite material; the polymer resin and the powder phase are dehydrated to a moisture content of less than 0.01wt% before use;

[0010] The powder phase is low-activity magnesium oxide and phosphate in a mass ratio of 1:3-5; the phosphate is at least one of dihydrogen phosphate and monohydrogen phosphate; the preparation method of the low-activity magnesium oxide comprises: heating the magnesium oxide to 1400-1600° C. at a heating rate of no more than 10° C. / min and calcining at this temperature for 3-6 hours to obtain the low-activity magnesium oxide;

[0011] S2, saturating the composite material in a physical foaming agent to obtain a saturated system, and then releasing pressure for foaming to obtain an open-cell material; the pressure of the physical foaming agent is 5 to 25 MPa; and the pressure relief rate of the pressure relief foaming is 10 to 100 MPa / s;

[0012] S3, immersing the open-pored material in water, allowing the low-activity magnesium oxide and the phosphate to react to generate bone cement, thereby increasing the strength of the open-pored material to obtain the high-strength open-pored material.

[0013] The phosphate used in the present invention is at least one of dihydrogen phosphate and monohydrogen phosphate. The magnesium phosphate cement reaction used in the present invention is that magnesium oxide generates magnesium hydroxide in an acidic environment, and then reacts with hydrogen in the phosphate, which is an acid-base neutralization reaction.

[0014] In one embodiment, in step S1, the total mass of the polymer resin and the powder phase is 100 parts.

[0015] In the preparation method of the low-activity magnesium oxide, the heating rate cannot be higher than 10°C / min, otherwise the activity of the magnesium oxide will be relatively high, and it is easy to react with phosphate to form bone cement before forming an open-porous material, making it difficult to prepare the desired open-porous material.

[0016] In the preparation method of the high-strength open-pored material, the polymer resin can be at least one of polylactic acid, polybutylene succinate, polycaprolactone, polypropylene carbonate, and polybutylene terephthalate-adipate.

[0017] Preferably, in the method for preparing the high-strength open-cell material, the storage modulus of the composite material is less than 100 Pa, which is conducive to the preparation of the open-cell foam material. The present invention uses a rotational rheometer to test the storage modulus of the composite material. First, the melting point of the composite material is measured according to a differential scanning calorimeter (DSC). The temperature of the storage modulus test is the melting point of the composite material + (4 to 30) ° C, the storage modulus test frequency is 0.01 rad / s to 0.1 rad / s, and the storage modulus of the composite material needs to be <1.0*10 2 Pa is beneficial to the preparation of the open-pored material.

[0018] In one embodiment, in the method for preparing the high-strength open-pored material, the particle size of the low-activity magnesium oxide is less than 200 mesh.

[0019] In the preparation method of the high-strength open-pored material, the phosphate can be at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, calcium dihydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate and disodium hydrogen phosphate.

[0020] The present invention requires that after the open-porous material is prepared, it will react with water to generate bone cement to improve the strength of the open-porous material. By reducing the moisture content in the raw material as much as possible, it is possible to avoid the reaction to generate bone cement before the open-porous material is formed, which makes it difficult to obtain the desired open-porous material. In the preparation method of the high-strength open-porous material, in step S1, the polymer resin and the powder phase are first dehydrated to a moisture content of less than 0.01wt% before use.

[0021] In one embodiment, in the method for preparing the high-strength open-pored material, in step S2, the saturation treatment includes a first saturation stage and a second saturation stage, the temperature of the first saturation stage is greater than or equal to the melting temperature of the composite material, and the crystal region of the composite material can be completely melted, which is conducive to the entry of more physical foaming agents, and the temperature of the second saturation stage is lower than the temperature of the first saturation stage. In one embodiment, the absolute value of the difference between the temperature of the first saturation stage and the melting temperature of the composite material is 4 to 100°C. In one embodiment, the cooling rate from the first saturation stage to the second saturation stage is 1 to 30°C / min.

[0022] In one embodiment, in the method for preparing the high-strength open-cell material, in step S2, the physical foaming agent is carbon dioxide and / or nitrogen.

[0023] In one embodiment, in the method for preparing the high-strength open-pored material, the open-pored material has an open porosity greater than 80%, so as to facilitate the full reaction of magnesium oxide and phosphate with water, thereby achieving the purpose of preparing the high-strength open-pored material.

[0024] In the method for preparing the high-strength open-pored material, in step S3, the reaction time of the open-pored material immersed in water can be selected according to needs, for example, the reaction time is not less than 10 minutes, and further, the reaction time can be 10 minutes to 1 hour.

[0025] The present invention introduces low-activity magnesium oxide and phosphate as fillers into a polymer matrix, and controls the water content of the polymer resin and powder phase mixture to avoid the reaction of magnesium oxide and phosphate to form bone cement before the preparation of the open-porous material, thereby preventing the polymer matrix from being strengthened and thus making it difficult to foam to form an open-porous material. The present invention further combines the regulation of the foaming process, immerses the prepared open-porous material in water, promotes the reaction of magnesium oxide and phosphate, generates bone cement, and improves the strength of the open-porous material. When the porosity of the open-porous material is low, it is not conducive to water immersion in the sample, and it is difficult to make the complete reaction of magnesium oxide and phosphate, which will weaken the effect of improving the strength of the open-porous material.

[0026] The present invention further provides a high-strength open-pored material prepared by the preparation method, which has broad application prospects in the field of tissue engineering.

[0027] The invention also provides application of the high-strength open-pored material in manufacturing a biological medical stent.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention processes magnesium oxide in a specific manner to convert it into low-activity magnesium oxide, and then mixes it with phosphate and polymer resin for melt extrusion to form a composite material. The composite material is further physically foamed to form an open-porous material. Finally, the open-porous material is immersed in water to allow the magnesium oxide and phosphate to react slowly and fully to form bone cement, thereby improving the strength of the open-porous material to obtain a high-strength open-porous material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope (SEM) photograph of the high-strength open-pored material prepared in Example 1 after compression.

[0031] Figure 2 This is a SEM photograph of the high-strength open-pored material prepared in Example 4 after stretching.

[0032] Figure 3 This is a SEM photograph of the high-strength open-pored material prepared in Example 4 after stretching. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0034] Example 1

[0035] Preparation: Magnesium oxide was heated from room temperature to 1600°C at a heating rate of 5°C / min and calcined in air at 1600°C for 4 hours, then cooled to room temperature, the obtained product was ground and passed through a 200-mesh sieve to obtain low-activity magnesium oxide. Polylactic acid (PLA) resin, low-activity magnesium oxide and potassium dihydrogen phosphate were dried in a vacuum oven at 80°C for 8 hours, and polycaprolactone (PCL) resin was dried in a vacuum oven at 40°C for 8 hours.

[0036] A mixture of 66 parts by mass of polylactic acid (PLA) resin, 20 parts by mass of polycaprolactone resin, 3 parts by mass of low-activity magnesium oxide and 11 parts by mass of potassium dihydrogen phosphate (all raw materials have been subjected to the above-mentioned drying process, and the moisture content of the mixture is 0.008wt%) is melt-extruded, air-cooled and pelletized to obtain composite material particles. Then, under the condition of 190°C, a pressure of 12MPa is used to hot-press the composite material particles into a polylactic acid-based composite material with a sheet structure of 1mm in thickness, and the melting point of the polylactic acid-based composite material tested by DSC is 161°C. The composite material is at a temperature of 170°C and the test frequency is 0.01rad / s to 0.1rad / s, and the measured sample storage modulus is 9.8 to 13.4Pa.

[0037] The polylactic acid-based composite material obtained above was placed in an autoclave, and carbon dioxide was introduced for a two-stage saturation treatment, wherein the pressure of the carbon dioxide was 20.0 MPa, the temperature of the first saturation stage was 165°C, and the saturation treatment time was 30 min. Then, the temperature was lowered to the second saturation stage at a rate of 10°C / min, the temperature of the second saturation stage was 85°C, and the saturation treatment time was 50 min, to obtain a saturated system.

[0038] The saturated system obtained above was depressurized at a rate of 10.0 MPa / s to prepare a polylactic acid-based foamed open-cell material with an expansion ratio of 3.1 and an open-cell ratio of 82.2%.

[0039] The prepared polylactic acid-based foamed open-cell material was placed in water at a temperature of 25°C for 50 minutes, then taken out and placed in air at room temperature for 24 hours. After the sample was dried in a vacuum oven, the compression strength of the sample was tested to be 26.6MPa and the tensile strength was 67.8MPa. The SEM test results of the sample after compression are as follows: Figure 1 shown.

[0040] Example 2

[0041] The only difference from Example 1 is that the temperature of the second saturation stage is 95° C. and the pressure is released at a rate of 100.0 MPa / s, and the rest are the same.

[0042] In Example 2, a polylactic acid-based foamed open-cell material was prepared, with an expansion ratio of 7.3 and an open-cell ratio of 87.9%.

[0043] The prepared polylactic acid-based foamed open-cell material was placed in water at a temperature of 25°C for 50 minutes, and then taken out and placed in air at room temperature for 24 hours. After the sample was dried in a vacuum oven, the compressive strength of the tested sample was 21.2 MPa and the tensile strength was 60.1 MPa.

[0044] Example 3

[0045] The only difference from Example 2 is that the pressure of carbon dioxide is 8 MPa, and the rest are the same.

[0046] In Example 3, a polylactic acid-based foamed open-cell material was prepared, with an expansion ratio of 4.4 and an open-cell ratio of 83.7%.

[0047] The prepared polylactic acid-based foamed open-cell material was placed in water at a temperature of 25°C for 50 minutes, and then taken out and placed in air at room temperature for 24 hours. After the sample was dried in a vacuum oven, the compressive strength of the tested sample was 24.6 MPa and the tensile strength was 63.4 MPa.

[0048] Example 4

[0049] The material preparation process is the same as in Example 1.

[0050] A mixture containing 70 parts by mass of polylactic acid (PLA) resin, 20 parts by mass of polycaprolactone resin, 2 parts by mass of low-activity magnesium oxide and 8 parts by mass of potassium dihydrogen phosphate was melt-extruded, air-cooled and pelletized to obtain composite particles. Then, the composite particles were hot-pressed into a polylactic acid-based composite material with a thickness of 1 mm at a pressure of 12 MPa under the condition of 190°C, and the melting point of the polylactic acid-based composite material was tested by DSC to be 160°C. The composite material was tested at a temperature of 170°C and a frequency of 0.01 rad / s to 0.1 rad / s, and the storage modulus of the sample measured was 8.1 to 12.1 Pa.

[0051] The polylactic acid-based composite material obtained above was placed in an autoclave, and carbon dioxide was introduced for a two-stage saturation treatment, wherein the pressure of the carbon dioxide was 15.0 MPa, the temperature of the first saturation stage was 165°C, and the saturation treatment time was 30 min. Then, the temperature was lowered to the second saturation stage at a rate of 10°C / min, the temperature of the second saturation stage was 105°C, and the saturation treatment time was 50 min, to obtain a saturated system.

[0052] The saturated system obtained above was depressurized at a rate of 30.0 MPa / s to prepare a polylactic acid-based foamed open-cell material with an expansion ratio of 12.1 and an open-cell ratio of 95.1%.

[0053] The prepared polylactic acid-based foamed open-cell material was placed in water at a temperature of 25°C for 40 minutes, then taken out and placed in air at room temperature for 24 hours. After the sample was dried in a vacuum oven, the compression strength of the sample was tested to be 17.7MPa and the tensile strength was 28.3MPa. The SEM test results of the sample after stretching are as follows Figure 2 shown.

[0054] Example 5

[0055] Preparation: Magnesium oxide was heated from room temperature to 1600°C at a heating rate of 5°C / min and calcined in air at 1600°C for 4 hours, then cooled to room temperature, the obtained product was ground and passed through a 200-mesh sieve to obtain low-activity magnesium oxide. Polylactic acid (PLA) resin, low-activity magnesium oxide and calcium dihydrogen phosphate were dried in a vacuum oven at 80°C for 8 hours, and polybutylene succinate (PBS) resin was dried in a vacuum oven at 60°C for 8 hours.

[0056] A mixture of 80 parts by weight of PBS resin, 6 parts by weight of PLA resin, 3 parts by weight of low-activity magnesium oxide and 11 parts by weight of calcium dihydrogen phosphate (all raw materials have been subjected to the above-mentioned drying process, and the moisture content of the mixture is 0.008wt%) is melt-extruded, air-cooled and pelletized to obtain composite material particles. Then, the composite material particles are hot-pressed into a PBS-based composite material with a sheet structure of 1mm in thickness at a pressure of 10MPa under the condition of 140°C, and the melting point of the PBS-based composite material tested by DSC is 114°C. The composite material has a storage modulus of 10.1 to 13.9Pa at a temperature of 120°C and a test frequency of 0.01rad / s to 0.1rad / s.

[0057] The PBS-based composite material obtained above was placed in an autoclave, and carbon dioxide was introduced for a two-stage saturation treatment, wherein the pressure of the carbon dioxide was 20.0 MPa, the temperature of the first saturation stage was 120°C, and the saturation treatment time was 30 min. Then, the temperature was lowered to the second saturation stage at a rate of 10°C / min, the temperature of the second saturation stage was 95°C, and the saturation treatment time was 50 min, to obtain a saturated system.

[0058] The saturated system obtained above was depressurized at a rate of 30.0 MPa / s to prepare a PBS-based foamed open-cell material with an expansion ratio of 15.7 and an open-cell ratio of 97.6%.

[0059] The prepared PBS-based foamed open-cell material was placed in water at a temperature of 25°C for 40 minutes, then taken out and placed in air at room temperature for 24 hours. The sample was dried in a vacuum oven and the compression strength of the sample was tested to be 10.6MPa and the tensile strength was 17.4MPa. The SEM test results of the sample after stretching are as follows: Figure 3shown.

[0060] Comparative Example 1

[0061] The only difference from Example 1 is that the heating rate of magnesium oxide during the material preparation process is 20° C. / min, and the rest is the same.

[0062] Comparative Example 1 was depressurized to prepare a polylactic acid-based foamed porous material with an expansion ratio of 1.1 and an open porosity of less than 5%.

[0063] Comparative Example 2

[0064] The only difference from Example 1 is that the pressure of carbon dioxide is 3 MPa, and the saturated system is depressurized at a rate of 5 MPa / s, and the rest are the same.

[0065] Comparative Example 2 was decompressed to prepare a polylactic acid-based foamed porous material with an expansion ratio of 2.7 and an open porosity of less than 10%.

[0066] Comparative Example 3

[0067] The only difference from Example 1 is that during the preparation process, the magnesium oxide is heated from room temperature to 1300° C. at a heating rate of 5° C. / min and calcined in air at 1300° C. for 4 h, and the rest is the same.

[0068] Comparative Example 3: The polylactic acid-based foamed porous material was prepared by decompression, with an expansion ratio of 1.9 and an open porosity of less than 5%.

[0069] Comparative Example 4

[0070] The only difference from Example 1 is that all raw materials have not been dried, the moisture content of the mixture is 3.6 wt %, and the rest are the same.

[0071] Comparative Example 4 is difficult to prepare a porous structure material.

[0072] Comparative Example 5

[0073] The only difference from Example 1 is that low-activity magnesium oxide and potassium dihydrogen phosphate are not added, and the rest are the same.

[0074] Comparative Example 5 prepared a polylactic acid-based foamed open-cell material with an expansion ratio of 14.7 and an open-cell ratio of 92.3%.

[0075] The prepared polylactic acid-based foamed open-cell material was placed in water at a temperature of 25°C for 50 minutes, then taken out and placed in air at room temperature for 24 hours. The sample was dried in a vacuum oven and the compressive strength of the tested sample was 1.7 MPa and the tensile strength was 12.8 MPa.

[0076] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a high-strength open-pored material, characterized in that: Includes steps: S1, mixing 85-99.99 parts by weight of a polymer resin and 0.01-15 parts by weight of a powder phase and melt-extruding to obtain a composite material; the polymer resin and the powder phase are dehydrated to a moisture content of less than 0.01wt% before use; The powder phase is low-activity magnesium oxide and phosphate in a mass ratio of 1:3-5; the phosphate is at least one of dihydrogen phosphate and monohydrogen phosphate; the preparation method of the low-activity magnesium oxide comprises: heating the magnesium oxide to 1400-1600° C. at a heating rate of no more than 10° C. / min and calcining at this temperature for 3-6 hours to obtain the low-activity magnesium oxide; S2, saturating the composite material in a physical foaming agent to obtain a saturated system, and then releasing pressure for foaming to obtain an open-cell material; the pressure of the physical foaming agent is 5 to 25 MPa; and the pressure relief rate of the pressure relief foaming is 10 to 100 MPa / s; S3, immersing the open-pored material in water, allowing the low-activity magnesium oxide and the phosphate to react to generate bone cement, thereby increasing the strength of the open-pored material to obtain the high-strength open-pored material.

2. The preparation method according to claim 1, characterized in that: The polymer resin is at least one of polylactic acid, polybutylene succinate, polycaprolactone, polypropylene carbonate, and polybutylene terephthalate-adipate.

3. The preparation method according to claim 1, characterized in that: The storage modulus of the composite material is less than 100 Pa; the storage modulus test temperature is the melting point of the composite material + (4-30)° C., and the storage modulus test frequency is 0.01 rad / s to 0.1 rad / s.

4. The preparation method according to claim 1, characterized in that: The particle size of the low-activity magnesium oxide is less than 200 meshes.

5. The preparation method according to claim 1, characterized in that: The phosphate is at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, calcium dihydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate and disodium hydrogen phosphate.

6. The preparation method according to claim 1, characterized in that: In step S2: The saturation treatment includes a first saturation stage and a second saturation stage, the temperature of the first saturation stage is greater than or equal to the melting temperature of the composite material, and the temperature of the second saturation stage is lower than the temperature of the first saturation stage; The physical foaming agent is carbon dioxide and / or nitrogen; The cooling rate from the first saturation stage to the second saturation stage is 1 to 30° C. / min.

7. The preparation method according to claim 6, characterized in that: The absolute value of the difference between the temperature of the first saturation stage and the melting temperature of the composite material is 4 to 100°C.

8. The preparation method according to claim 1, characterized in that: The open-pore material has an open-pore ratio greater than 80%.

9. The high-strength open-pored material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the high-strength open-pored material according to claim 9 in the manufacture of biological medical stents.

Citation Information

Patent Citations

  • Open-cell polylactic acid foam material and preparation method thereof

    CN114752097A

  • 3D printable magnesium phosphate bone cement as well as preparation method and application thereof

    CN109437826A

  • Mesoporous calcium magnesium silicate / magnesium ammonium phosphate composite material and method for preparing bone cement and skeleton by using composite material

    CN112717206A

  • Polylactic acid-based foam material and preparation method thereof

    CN113736128A

  • Manufacture method of inorganic foam using magnesia and its hardner at room temperature

    KR1020130040083A